The hope jar - Brunstetter, Wanda E. (Shiloh Run Press, an imprint of Barbour Publishing, Inc., 2018)
"Michelle Taylor is not who her new family in Lancaster County believes her to be. The Lapps were looking for their long-lost granddaughter when they met Michelle and she assumed the identity of Sara Murray. Once homeless and hopeless, Michelle has come to love her new Amish friends and even considers the idea of romance among them. Finding an old blue jar in the barn that is filled with slips of paper with handwritten thoughts, quotes, and prayers by an unknown author encourages Michelle's budding faith--but she also finds herself feeling [conflicted]. How can she tell the truth without hurting the ones she has truly come to love?" -- Page [4] of cover.
Keywords: Impostors and imposture -- Fiction; Amish -- Fiction; Lancaster County (Pa.) -- Fiction; Romance fiction; Christian fiction; Love stories